Seismic Performance Evaluation using Pushover Analysis of Four Two-Storey Residential Building Types in West Bandung Regency - Joesack Renaldi Sugianto; Yosafat Aji Pranata (Journal of Green Science and Technology, 2026)
In seismic-actively located West Bandung Regency it is crucial for evaluation of existing residential buildings seismic performance to mitigate potential earthquake losses. The purpose of this study was to study four standard two-storey reinforced concrete residential houses type A–D in West Bandung Regency using nonlinear static pushover analysis in SAP2000 and two main directions (X and Y). Performance points were established using the FEMA 440 equivalent linearization approach by crossing the capacity spectrum with the seismic demand spectrum, including stiffness degradation and effective damping due to nonlinear response. The seismic performance was analyzed in terms of some of the most common response indicators (spectral acceleration, spectral displacement, effective period or ductility, effective damping) and an empirical FEMA 356 plastic hinge assessment to establish the dominant mechanism of the damage. This shows a high directional dependency between spectral demand and displacement capacity among building types. The distribution of hinge states at the performance point is characterized by early–to-moderate damage types (A–B, B–IO, and IO–LS), with more severe states (LS–CP, CP–C, and isolated C–D) present in certain situations and localized. In conclusion the nonlinearity of the response is best characterized by a beam dominant mechanism indicating ductile behavior, however localized advanced hinge states indicate the requirement for targeted strengthening at critical members and directions.